2022
DOI: 10.3389/fmars.2022.829419
|View full text |Cite
|
Sign up to set email alerts
|

Predator Field and Colony Morphology Determine the Defensive Benefit of Colony Formation in Marine Phytoplankton

Abstract: Colony formation in marine phytoplankton can be modified by the presence of grazers, but the effect of colony size and shape on the feeding behavior of grazers is still relatively unknown. To explore the defensive role of colony formation, we examined the feeding response of three differently sized grazers (copepodites, copepod nauplii, and two heterotrophic dinoflagellates) feeding on colony-forming phytoplankton, using both direct video observations and bottle incubations. We found a dramatic increase in cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Many diatoms may further harness this defense by thickening the shell in response to copepod cues (Pondaven et al 2007;Grønning and Kiørboe 2020). Other inducible defense mechanisms include the modification of colony size in some chainforming diatoms-shorter chains reduce the risk of being consumed by a copepod (Rigby and Selander 2021;Ryderheim et al 2022b)-and the production of toxins in Pseudo-nitzschia species that make copepods deselect toxin-producing cells (Zhang et al 2021;Olesen et al 2022). It has similarly been described that viral infection induces formation of resting spores that may subsequently germinate as healthy cells (Pelusi et al 2021), and viral infections can also cause aggregation and mass sinking (Yamada et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many diatoms may further harness this defense by thickening the shell in response to copepod cues (Pondaven et al 2007;Grønning and Kiørboe 2020). Other inducible defense mechanisms include the modification of colony size in some chainforming diatoms-shorter chains reduce the risk of being consumed by a copepod (Rigby and Selander 2021;Ryderheim et al 2022b)-and the production of toxins in Pseudo-nitzschia species that make copepods deselect toxin-producing cells (Zhang et al 2021;Olesen et al 2022). It has similarly been described that viral infection induces formation of resting spores that may subsequently germinate as healthy cells (Pelusi et al 2021), and viral infections can also cause aggregation and mass sinking (Yamada et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have demonstrated yet another potential defense mechanism, the formation of aggregates in response to copepod cues. While small aggregates may be consumed by copepods at higher rates than solitary cells, aggregates will sink to the ocean interior or the seafloor where predation mortality is low Josefson 2001, 2004;Ryderheim et al 2022b). Sinking aggregates may be colonized by copepods and other zooplankton that may graze on the aggregated cells (Kiørboe 2000;Koski et al 2017), but increased stickiness will speed up aggregation and lead to larger aggregates with high sinking speeds and, hence, short residence time in the water column.…”
Section: Discussionmentioning
confidence: 99%
“…Colony formation in marine phytoplankton provides benefit against grazers ( 42 ), and it is possible that Trichodesmium colony formation can reduce the rates of predation by particular classes of zooplankton, possibly due to biotoxin accumulation ( 43 , 44 ). The reduction of grazing could boost colony success against free trichomes, but such a reduction should compensate for the lowered C fixation and N fixation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we will separate these from the analysis of other Temora longicornis capture events that end in prey ingestion, since the handling time here may be underestimated compared to a "rigid" cell or colony of similar size (Jansen 2008). During prey rejection, however, colonies remain intact (Ryderheim et al 2022b), and we thus include them in this analysis. Complete data on P. globosa can be found in the supplement (Supporting Information Fig.…”
Section: Data Processingmentioning
confidence: 99%
“…However, prey‐handling times may vary between copepods with different feeding modes and are in addition influenced by several prey‐related factors. Generally, larger prey take longer to handle and ingest (Rao and Kumar 2002; Tiselius et al 2013; Gonçalves et al 2014; Ryderheim et al 2022 b ), and more recently it was found that diatoms with thicker shells are handled for a significantly longer time than those with thin shells (Ryderheim et al 2022 a ). Also, copepods are known to be very selective feeders (Teegarden 1999; Leitão et al 2018) and may handle but reject a large fraction of captured prey, which may thus further detract from the time available for searching new prey (Jeschke et al 2002).…”
mentioning
confidence: 99%